Protein Arginine Methylation in Parasitic Protozoa - Fisk, John C. (American Society for Microbiology, 2011)
Protozoa constitute the earliest branch of the eukaryotic lineage, and several groups of protozoans are serious parasites of humans and other animals. Better understanding of biochemical pathways that are either in common with or divergent from those of higher eukaryotes is integral in the defense against these parasites. In yeast and humans, the posttranslational methylation of arginine residues in proteins affects myriad cellular processes, including transcription, RNA processing, DNA replication and repair, and signal transduction. The protein arginine methyltransferases (PRMTs) that catalyze these reactions, which are unique to the eukaryotic kingdom of organisms, first become evident in protozoa. In this review, we focus on the current understanding of arginine methylation in multiple species of parasitic protozoa, including Trichomonas, Entamoeba, Toxoplasma, Plasmodium, and Trypanosoma spp., and discuss how arginine methylation may play important and unique roles in each type of parasite. We mine available genomic and transcriptomic data to inventory the families of PRMTs in different parasites and the changes in their abundance during the life cycle. We further review the limited functional studies on the roles of arginine methylation in parasites, including epigenetic regulation in Apicomplexa and RNA processing in trypanosomes. Interestingly, each of the parasites considered herein has significantly differing sets of PRMTs, and we speculate on the importance of this diversity in aspects of parasite biology, such as differentiation and antigenic variation.